2021
DOI: 10.3329/ijarit.v10i2.51574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of black cumin genotypes for yield and yield related parameters in bale mid altitude, southeastern Ethiopia

Abstract: Fourteen black cumin genotypes were evaluated against standard checks for two consecutive years during 2018 to 2019 at Sinana, Goro and Gindhir to investigate high yielder and stable black cumin varieties. The mean total seed yield of genotypes across environment ranged from 24.54 to 16.07 Qt ha-1. The highest total seed yield was recorded from genotypes 242826-2 followed by 242826-2 (24.54 and 23.32 Qt ha-1) while the lowest total seed yield was obtained from local checks. These two genotypes have yield advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Similarly, the highest mean thousand seed weight (2.66 g) was also recorded from the genotype 242840 followed by genotype 242841 (2.59 g); while the lowest thousand seed weight (1.95 g) was recorded from Aden variety. Similar findings were reported by Miheretu (2016); Girma et al (2016) and Getachew and Beriso (2020), who indicated that black cumin seed yield is significant with plant height, number of capsules plant -1 , number of primary branches plant -1 , and number of seeds capsule -1 . Other researcher's Ermias et al (2015); Miheretu, (2018) reported the existence of significant differences among black cumin genotypes for phenological and growth parameters including days to 50% flowering, days to 90% maturity, plant height, number of primary and secondary branches, yield components (number of capsules and number of seeds capsule -1 ) and seed yield.…”
Section: Fikre Et Al 2023supporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the highest mean thousand seed weight (2.66 g) was also recorded from the genotype 242840 followed by genotype 242841 (2.59 g); while the lowest thousand seed weight (1.95 g) was recorded from Aden variety. Similar findings were reported by Miheretu (2016); Girma et al (2016) and Getachew and Beriso (2020), who indicated that black cumin seed yield is significant with plant height, number of capsules plant -1 , number of primary branches plant -1 , and number of seeds capsule -1 . Other researcher's Ermias et al (2015); Miheretu, (2018) reported the existence of significant differences among black cumin genotypes for phenological and growth parameters including days to 50% flowering, days to 90% maturity, plant height, number of primary and secondary branches, yield components (number of capsules and number of seeds capsule -1 ) and seed yield.…”
Section: Fikre Et Al 2023supporting
confidence: 89%
“…The national average productivity of black cumin was reported to be 0.79 t ha -1 (Habtewold et al, 2017); while Zigyalew (2020) reported 0.64 t ha -1 , which is well below the global average and some major producing countries including India (2.2 t ha -1 ). However, high seed yield up to 1.7 t ha -1 at Adet, 1.8 t ha -1 at Woreta and 2.45 t ha -1 at Bale in Ethiopia were obtained (Adam, 2007, Getachew andBeriso, 2020). The low yields are mainly due to the low productivity of the varieties (Ermias et al, 2015) among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the highest significant grain yield was reported at 20kg/ha seed rate for local varieties in northern Ethiopia (Yemisrach et al, 2008); while 5-7.5kg/ha (Minstry of Agriculture and Rural Developement, 2006) and 15-20kg/ha reported for released varieties (Minstry of Agriculture and Rural Developement, 2009). Variation in the adaptability of different varieties including the released one was also reported at different growing environments where maximum yield was observed for local varieties as compared to the released varieties at the Kafa zone of southwestern Ethiopia (Ermias et al, 2015); whereas the released varieties Dirshaye and Aden were recommended for west Hararghe zone mid highlands, eastern Ethiopia (Gezahegn and Sintayehu, 2016), Darbera variety performed best as compared to other released and local varieties at mid-altitude of Bale, southeastern Ethiopia (Asefa and Beriso, 2020), and the released variety Aden at 10kg/ha seed rate performed best at Burusa of Oromiya region (Mahbuba et al, 2021). These variations reported for different black cumin varieties under different seed rates and locations call for the importance of specific area research recommendations.…”
mentioning
confidence: 91%